Rethinking Student Success in HEIs: A Validation study of Holistic Student Development - Ms. Mani Goswami,; Prof. Sunil Dhal, (The Bioscan, 2026)
Purpose: The objective of this study is to develop and psychometrically validate a Holistic Student Development Measurement Scale (HSDMS) based on multidimensional theoretical framework which is laid out in the National Education Policy (NEP) 2020 for Indian HEIs. Design/Methodology/Approach: A systematic approach of scale development which is a mix of qualitative and quantitative methods is used. Phase I comprises of Focus Group Discussions (FGDs), Systematic Literature Review (SLR), item generation (60 items), face validation and content validation by the Content Validity Index (CVI). A pilot study (n = 104) was conducted before the large scale data collection, which was done from 1,067 students from three HEIs in India adopting multistage stratified sampling technique. After data cleaning, 995 valid responses were randomly divided into two sets: One for Exploratory Factor Analysis (EFA) with 490 responses and the other for Confirmatory Factor Analysis (CFA) with 505 responses. Result: Principal Component Analysis revealed five factors namely Physical Quotient (PQ), Emotional Intelligence Quotient (EIQ), Social Intelligence Quotient (SIQ), Intellectual Quotient (IQ), and Spiritual Intelligence Quotient (SpIQ) with 32 items and explained around 66% of total variance. CFA on the independent subsample confirmed the five-factor structure with satisfactory model fit: χ²/df = 2.31, GFI = 0.92, AGFI = 0.90, CFI = 0.95, TLI = 0.94, IFI = 0.95, RMSEA = 0.050, SRMR = 0.048. The Cronbach's alpha (α) coefficient varied from 0.87 to 0.93 for each construct. The results showed that the Composite Reliability (CR) was ranging from 0.89 to 0.94 and Average Variance Extracted (AVE) range from 0.61 to 0.66, which indicate convergent validity. The Fornell-Larcker criterion was used to determine the discriminant validity. Originality/Value: This study introduces one of the first rigorously validated, multidimensional HSDMS in the HEI context explicitly aligned with NEP 2020 framework. The scale provides a valid and culturally relevant instrument for evaluating and improving student outcomes across the entire student experience for institutional administrators, policymakers, accreditation agencies, and researchers.